(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: The study titled survey on treatment adherence and related factors among patients with endophthalmitis at the Vitreoretinal Department, Ho Chi Minh city Eye Hospital to evaluate and improve treatment effectiveness. Method: The study utilized the MMAS-8 scale (Cronbach’s Alpha = 0.83) to measure medication adherence behavior and a non-medication adherence questionnaire (Cronbach’s Alpha = 0.7) to assess non-medication adherence. Results: The medication adherence rate was 82.7% (MMAS-8 score ≥ 6), while the non-medication adherence rate was 65.3% (score ≥ 8/10). The study found that medication adherence was associated with occupation (civil servants were 1.3 times more adherent than farmers), educational level (those who were literate had 41% lower adherence, and those with primary education had 32% lower adherence compared to the illiterate group), and comorbidities (patients with asthma/COPD were 1.49 times more adherent than those without). Conclusion: The study provides a foundation for improving adherence guidance and enhancing treatment quality in the Vitreoretinal Department, Ho Chi Minh city Eye Hospital.